2008
DOI: 10.1111/j.1440-1746.2008.05320.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Th1/Th2 ratio during a 24‐week course of an interferon alpha‐2b plus ribavirin combination therapy for patients with chronic hepatitis C

Abstract: The significant changes in the Th2 level correlated with the therapeutic effect during the IFN alpha-2b plus ribavirin combination therapy. The increase of the Th2 level during therapy could be a predictor for achieving SVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Initially, it was reported that ribavirin enhances production of T helper 1 (Th1) cytokines such as IFN-γ, TNF-α and IL-2, while suppressing T helper 2 (Th2) cytokines such as IL-4, IL-5 and IL-10 (11,12). However, contradictory results have been reported by other studies (13), thus T cell-regulatory roles of ribavirin are still controversial (14). …”
Section: Introductionmentioning
confidence: 93%
“…Initially, it was reported that ribavirin enhances production of T helper 1 (Th1) cytokines such as IFN-γ, TNF-α and IL-2, while suppressing T helper 2 (Th2) cytokines such as IL-4, IL-5 and IL-10 (11,12). However, contradictory results have been reported by other studies (13), thus T cell-regulatory roles of ribavirin are still controversial (14). …”
Section: Introductionmentioning
confidence: 93%
“…Several studies showed an association between the abundance of TCD8+ cells and SVR 14,22 , and the quality of the T helper (Th)1 response in the baseline period, and the increase in Th2 cytokines during treatment may define treatment success or failure 11,14,23,24 . These studies were performed on patients treated with dual therapy (IFN alpha or PegIFN and RBV).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HCV treatment has been demonstrated to lead to lymphocyte polarization towards Th1 over Th2, a mechanism implicated in the pathogenesis of PBC. 8 Some obscure points need to be considered. For example, normal alkaline phosphatase levels are unusual in PBC, but some reports in literature have highlighted this eventuality.…”
mentioning
confidence: 99%